The Challenges and Opportunities of Pre-Marriage Counselling in Hungary: A Flexible Model (European Journal of Mental Health, 2015)
A Flexible Model: The article offers an overview of the obstacles, challenges and opportunities of pre-marriage counsellor and facilitator training in Hungary. It presents the first institutionally affiliated pre-marriage counselling program and the corresponding facilitator training. It summarises the feedback from the test course participants (eight couples and nine priests), and reviews options for development.